Haliplidae, Noteridae, Dytiscidae (Coleoptera) du Gabon (9ème partie). Parc National des Plateaux Batéké (missions 2010 et 2012) - Armando Bilardo; Saverio Rocchi (Natural History Sciences, 2013)
Haliplidae, Noteridae, Dytiscidae (Coleoptera) of Gabon (9th part). Plateaux Batéké National Park (missions 2010 and2012). This work concerns the Coleoptera Hydradephaga collected in three localities of Plateaux Batéké National Park (Republic of Gabon) and in two localities external to the Park in two missions (2010 and 2012), in which altogether 82 species are listed (13 Noteridae and 69 Dytiscidae); considering also the species collected in previous missions (2005, 2006, 2007, 2008) in all 18 visited localities altogether 155 species are listed (1 Haliplidae, 17 Noteridae and 137 Dytiscidae). The Authors describe three new species: Bidessus batekensis (group sharpi, subgroup ovoideus) near B. toumodiensis Guignot, 1939, distinguishable by dark brown elytra without net testaceous longitudinal markings and by penis; Copelatus tondangoyei (group erichsoni, subgroup atrosulcatus) distinguishable from close species by penis; Copelatus fizpaci (group longicornis, subgroup guerini) closed to C. ateles Guignot, 1955, distinguishable by bigger size and by penis. Besides some types of species of the genus Copelatus Erichson, 1832 examined have permitted the description of other african species: C. sylvaticoides (group irinus, subgroup irinus). Some observations concerning species of Copelatus genus, that have dentate penis, are reported.